Behavioral and social science research to support development of educational materials for clinical trials of broadly neutralizing antibodies for HIV treatment and prevention. (February 2021) - Valente, Pablo K; Wu, Yumeng; Cohen, Yehuda Z; Caskey, Marina; Meyers, Kathrine
Background/Aims: Early integration of behavioral and social sciences research into clinical trials can improve trial conduct and facilitate future implementation of biomedical interventions. We sought to examine participants' experiences in clinical trials with broadly neutralizing antibodies and describe the development of educational materials for use in future broadly neutralizing antibody research. Methods: We conducted semi-structured interviews with trial participants in phase 1 trials evaluating safety and efficacy of broadly neutralizing antibodies for HIV prevention and treatment and key informants (i.e. trial staff involved in broadly neutralizing antibody research). Semi-structured interviews were transcribed and analyzed thematically. Based on findings from the interviews, we developed educational materials addressing concerns and misconceptions identified among trial participants with input from community and research stakeholders. Educational materials were used in subsequent clinical trials with broadly neutralizing antibodies. We evaluated trial staff's experiences with newly developed educational materials in follow-up key informant interviews. Results: Although most participants were concerned about long-term harms related to the investigational product upon enrollment, absence of severe side effects in the trial led to an underestimation of risks related to the study during trial participation. Participants showed a poor understanding of what broadly neutralizing antibodies are and the differences between broadly neutralizing antibodies and other HIV prevention and treatment products, such as antiretrovirals. Many trial participants overestimated the possible public health impact of the broadly neutralizing antibody trials in which they were enrolled, associating broadly neutralizing antibody research with the development of vaccine or cure for HIV in the near future. Based on these concerns and misconceptions among trial participants, we developed a frequently asked questions document and adapted an existing educational video about broadly neutralizing antibodies. In follow-up interviews, key informants reported that materials helped address trial participants' concerns and questions related to the trial. Key informants reported using the educational materials not only during informed consent but also throughout trial participation, which contributed to making informed consent an "ongoing" process. Conclusion: Integration of behavioral research into clinical trials with broadly neutralizing antibodies is key to identify and address key concerns among trial participants. Behavioral and social sciences research promotes communication between trial participants and biomedical researchers, facilitates engagement of participants and trial staff, and strengthens trial conduct. Development of educational materials collaboratively by behavioral and clinical scientists, trial staff, and community stakeholders is feasible and may help to address trial participants' concerns and misconceptions. Future research should evaluate the impact of educational materials in recruitment and retention of trial participants.